Gendered Perceptions of Leadership in Brazil: Attitudinal Divides and Cultural Implications - Chullen, Cody L.; Barber III, Dennis; Adeyemi-Bello, Tope; Cavazotte, Flavia (Journal of Knowledge Management Practice, 2025)
This study explores gender-based attitudes toward women in managerial roles in Brazil using the Women as Managers Scale (WAMS). Informed by social learning and gender role socialization theories, responses from 375 participants reveal notable attitudinal differences between men and women on issues such as emotional regulation and leadership competence. The results provide new empirical insight into gender perceptions in Brazil’s workplace culture and highlight the need for targeted interventions, including inclusive policies, training programs, and educational efforts, to advance equitable leadership opportunities across sectors.